Pulsed Electron Deposition (PED) - a Novel Tool for Growth of Thin Films - Sang, Ngo Dinh; Quang, Pham Hong; Ngoc, Do Quang (Communications in Physics, 2012)
Pulsed Electron Deposition (PED) is a novel technique that can be applied for growing high quality thin films. In this technique, we used an electron beam with a focused diameter of about 1 mm, the energy up to 15 kV, the frequency of 1-10 Hz, the pulse width of 100 ns and the total current of 1.5 kA generated in a discharge system. A remarkable advantage of this technique is the low deviation in composition from bulk to film. By using the PED technique the transparent coducting ZnO and Cu(InGa)Se\(_{2 }\) films were prepared. The effect of some deposition conditions on the properties of film has been examined and discussed. For Cu(InGa)Se\(_{2 }\), the best film was obtained at the discharge voltage of 12 kV and substrate temperature of 400\(^°\)C, while for ZnO, the best film was grown at the oxygen pressure of 1.3 Pa and at 400(^°\)C.